The research of clinker monominerals modified suspensions’ rheological properties - M M, Kosukhin; I V, Starostina; A M, Kosukhin (International Journal of Engineering and Technology, 2018)
The findings of studying the influence of the superplasticizers of various natures on rheological properties of clinker monomineralsâ€™ water suspensions have been presented. It has been shown that the plasticizing activity of admixtures is determined by the nature and the specific surface of a monomineral and the nature of the admixtureâ€™s hydrophilic groups, and for complex admixtures also with the ratio of individual components. The optimal admixture dosages for monomineral suspensions of clinker minerals change in the row C2S, C3S, C3A, C4AF, which allows forecasting the influence of admixtures on rheological properties of systems with cements of various mineral compositions. The obtained data correlate with the research findings of the admixturesâ€™ influence on cements of various mineral composition, which allows deducing the influence of admixtures on the systems with other cements, and providing the economically and technologically feasible selection and consumption of admixtures depending on the type of cement and its mineral composition.Â